Empirical investigation towards insurance client investment pattern and factors influence insurance client loyalty and insurance agent sales performance / Mohd Syafig Mohamed Yunus - Mohamed Yunus, Mohd Syafig (Bachelor of Science (Hons) Statistics, 2014)
Nowadays, in life insurance business good servicing is the best way to attract new prospect client as well as to increase the sales performance of the insurance agent. Since the client satisfaction is a most important thing that can influence client loyalty, it is appropriate to determine what factors exactly influence customer loyalty. Furthermore, to know the insurance agent job motivation and sales performance, it is also appropriate to determine what factors influence insurance agent job motivation and sales performance. The purpose of this study was to assess the impact of insurance client satisfaction towards insurance client loyalty and modeling factors influencing insurance client satisfaction, factors influencing insurance agent job motivation and factors influence insurance agent sales performance. A survey methodology using simple random sampling technique was carried out, covering insurance client and insurance agent from Prudential (Jaya33) branch, Petaling Jaya. A structured questionnaire was then distributed to 200 selected insurance clients and 200 insurance agents. In this study, simple linear regression analysis was employed to examine the impact of insurance client satisfaction towards insurance client loyalty. The result was found that, client satisfaction significantly influences insurance client loyalty. Where insurance client loyalty tends to increase if the client satisfaction becomes satisfy with the service received. Multiple linear regression was also used to identify the factors that influence insurance agent satisfaction. It was found that, perception towards agent influence insurance client satisfaction. It reveals that, insurance client satisfaction will increase if the perception towards insurance agent is good. Then, used multiple linear regression to identify the factors that influence insurance agent job motivation. It was found that job satisfaction influence insurance agent job motivation. It reveals that, insurance agent job motivation will increase if the insurance agents satisfy with the job that they do. Lastly, multiple linear regression was also used to identify the factors that influence insurance agent sales performance. Job motivation and job crafting were also found to be significantly influencing the insurance agent sales performance. Where it implied that the insurance agent sales performance would increase when they get motivated and hard work in doing their job. Since this study provided a basis for determining the factors contribute to the insurance client satisfaction, insurance agent job motivation and insurance agent sales performance, it is suggested that further research should be conducted covering more wide geographical area in order to gain more insight about the other factors that might influence insurance client satisfaction, insurance agent job motivation and insurance agent sales performance